Analysis of Gadget Use (Online Game Addiction) and Emotional Intelligence on Student Learning Motivation in Pandeglang City Senior High School - Devi Elisa; Septi Citra Permana; Christian Ericson (International Journal of Education, Information Technology, and Others, 2022)
The purpose of this study was to determine the effect of using gadgets (online game addiction) and emotional intelligence on students' learning motivation at SMAN 7 Pandeglang. The method used in this study is a survey method with a quantitative approach. Data collection techniques used instruments to measure online game addiction, emotional intelligence and instruments to measure students' learning motivation. Based on the results of data analysis and hypothesis testing with path analysis calculations, the results show that 1) there is an effect of gadget use (online game addiction) on learning motivation, 2) there is an influence of emotional intelligence on learning motivation, 3) there is an influence of online game addiction and emotional intelligence on learning motivation. student learning motivation at SMAN 7 Pandeglang. The longer the duration of the child in playing gadgets, the intelligence of the child will decrease. And of course it will affect the decrease in students' learning motivation